Comparison of chemical, physical, and ultrasound treatments on the shelf life of fresh-cut quince fruit (Cydonia oblonga Mill.) - Yildiz, Gulcin; İzli, Gökçen; Aadil, Rana Muhammad (Wiley, 2020)
The study was conducted to examine the effect of chemical treatment (ascorbic acid and calcium chloride), physical treatment (water bath at 65 degrees C), and ultrasound (US) in ultrasonic bath for the prevention of enzymatic browning of fresh-cut quince slices during 14 days of storage. The treated quince slices were analyzed in terms of color, polyphenol oxidase, and pectin methyl esterase activity, bioactive compounds, sensory, and microbial analysis. The results showed that US treatment inhibited (p < .05) the growth of bacteria, mold, and yeast in fresh-cut quince slices during 4 degrees C storage. The US-treated slices showed a significant (p < .05) improvements in bioactive compounds as well as improved physical properties as compared to all other treatments. Similarly, US-treated samples showed the best color values with the lowest value of enzyme activities showing less enzymatic browning. Moreover, the findings showed that the lowest score for decay and off-odor were obtained for the quinces treated with US. Practical applications A significant improvement in the quality of US-treated fresh-cut quinces with the comparison of other chemical and physical treatments was achieved. This study will contribute a novel method to develop US-treated fresh-cut fruit and vegetables with an enhanced product quality and extended shelf life. In overall, processing of fresh-cut quince fruit with a US treatment might be applied to get a high-quality and browning-free product.
Keywords: Ascorbic acid